THE EFFECT OF COMPANY GROWTH AND LEVERAGE ON FIRM VALUE WITH DIVIDEND POLICY AS A MODERATING VARIABLE - Afifah, Hanna Nur; Gurendrawati, Etty; Utaminingtyas, Tri Hesti (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of company growth and leverage on firm value with dividend policy as a moderator. Sampling in this study was carried out using purposive sampling method with a total sample of 17 food and beverages subsector companies during 2020-2022 and a total of 51 observations. The data used is secondary data taken from the Indonesia Stock Exchange (IDX) website. The data analysis method in this study is panel data regression and interaction analysis using moderated regression analysis (MRA). The test results show that company growth has a positive effect on firm value. Leverage has a negative effect on firm value. Dividend policy is able to moderate the effect of company growth on firm value. Dividend policy is not able to moderate the effect of leverage on firm value. Testing the independent variables with the f test proves that company growth, leverage, interaction of company growth with dividend policy, and interaction of leverage with dividend policy can affect firm value together.